Impact of a yeast‐based dietary supplement on the intestinal microbiome of rainbow trout, Oncorhynchus mykiss. (21st November 2020) - Hines, Ian S.; Ferguson, Clay S.; Bushman, Timothy J.; Gatlin, Delbert M.; Jensen, Roderick V.; Smith, Stephen A.; Kuhn, David D.; Stevens, Ann M.
Abstract: The microbiome, an important aspect of fish aquaculture, is influenced by exogenous factors in the rearing environment including the composition and nutrient quality of the diet. To reduce reliance on fishmeal, alternative protein sources including yeast ( Saccharomyces cerevisiae ), have been successfully used in many aquafeeds. To investigate the effect of supplemented lysed and dried yeast on the fish physiology, including the intestinal epithelial‐associated microbiome composition, rainbow trout ( Oncorhynchus mykiss ) were fed a standard commercial diet or one of four additional in‐house extruded experimental diets containing 0%, 20%, 40% or 60% yeast nutrient supplement as a menhaden fishmeal substitute for 16 weeks. The commercial diet, 0%, and 20% supplement‐fed fish had similar average weight gains that were significantly ( p < 0.05) higher in comparison to groups with a higher percentage of yeast. To examine if the yeast‐supplemented diet had any impact on the intestinal epithelial‐associated microbiome, both phylum‐ and family‐level comparisons of the microbial communities across treatments were made. The dominant families were Mycoplasmataceae and Fusobacteriaceae with Mycoplasma spp. and Cetobacterium somerae being the dominant organisms, respectively. Results from bioinformatics analysis showed little community variation between experimental diets, suggesting that lysed and dried yeast will serve as a dietary supplement without causing large shifts in the intestinal microbiome community.